Chair's note: a strategy to develop our geographical and interdisciplinary reach, and our potential audiences. (November 2020) - Atkinson, David
Abstract: The Society for Libyan Studies celebrated its 50th year in 2019 and it boasts a long record of promoting excellent research on Libya and its adjacent regions. Our second half-century will bring new challenges and opportunities. This note outlines our strategy to maintain our focus on Libya while acknowledging that Libya has always been embedded within wider networks of influence, trade and engagement across the Mediterranean and throughout North and Central Africa. We want to acknowledge this broader geographical remit more clearly with a new subtitle for this journal: Libyan Studies: a Journal of North African and Mediterranean Cultures . This subtitle also points to the benefits of engaging other academic communities beyond our traditional, core constituencies of archaeology, ancient history and history – not least because a broader engagement with contemporary research will help to maintain the Society's strength, relevance and sustainability. Likewise, we aim to engage more interest from the Libyan and North African diaspora in Britain. These initiatives will build upon our strong foundations to make us more able to respond to the challenges of our second 50 years.